Surgical Treatment of Pseudoaneurysm of Innominate Artery Infected with Burkholderia Pseudomallei - Roan, Jun-Neng (Zhonghua Minguo Xin Zang Xue Hui Za Zhi, 2013)
The management of melioidosis, caused by Burkholderia pseudomallei, presenting as an infected pseudoaneurysm requires radical debridement and prolonged antibiotics because the pathogen is resistant to host immunity. An extra-anatomical bypass might be a better treatment choice than in situ graft interposition or other methods.We report on a 76-year-oldman with an infected pseudoaneurysmlocated in the innominate artery and a method of extra-anatomical bypass that has not yet been reported in the literature. The patient recovered well without recurrence of infection after the surgical procedure.